(3GdEfOeGL GdeUQajs - (3eMSf GMeO(B, (3GdNVjQjs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI,s, 2007)
(3jVe Shb GdGfOeGL GdeUQaj GdeUQj, adSaI hKbGaI GdOeL GdeUQaj, JYQja GdGfOeGL GdeUQaj, CSHGH GdOeL, GfhGY GdGfOeGL GdeUQaj, CgOGa GdOeL GdeUQaj, eQGMd GdGfOeGL GdeUQaj, WQb hcjajI JMbjb GdGfOeGL GdeUQaj, efGgL GdGfOeGL GdeUQaj; eRGjG GdGfOeGL GdeUQaj, TQhW GdGfOeGL GdeUQaj, GOGQI YedjGJ GdOeL GdeUQaj, BdjGJ GdOeL GdeUQaj, QSGdI GdOeL, eJWdHGJ hpecOGJ fLGM YedjGJ GdOeL, eMGPjQ GdGfOeGL GdeUQaj, JcdaI GdGfOeGL GdeUQaj; GdfJGFL GdeJQJHI Ydi YedjGJ GdOeL GdeUQaj, eGHYO GdGeOeGL, BaGb heYGjjQ LOjOI ddGfOeGLs
Keywords: (3GdGOGQIs; (3GdHfhcs; (3GdJfXjes